Sequential systemic treatment in patients with hepatocellular carcinoma. Issue 1 (20th May 2020) - Kirstein, Martha M.; Scheiner, Bernhard; Marwede, Tristan; Wolf, Caroline; Voigtländer, Torsten; Semmler, Georg; Wacker, Frank; Manns, Michael P.; Hinrichs, Jan B.; Pinter, Matthias; Vogel, Arndt
Summary: Background: Hepatocellular carcinoma (HCC) is one of the most lethal cancers. After many years of stagnation, there are now several systemic treatments available for patients with HCC. Aim: To analyse the feasibility and efficacy of sequential systemic treatments in patients with HCC in clinical practice. Methods: In this multicentre study, patients who were treated with novel systemic therapies for HCC between 2014 and 2019 at two referral centres, Hannover Medical School, Germany, and Medical University of Vienna, Austria, were included. Results: Overall, 85 patients were included of which 76 patients (89.4%) received more than one and a maximum of five systemic treatment lines. The most common therapy sequence was sorafenib (n = 72; 84.7%) followed by regorafenib (n = 37; 48.7%), whereas 11 patients were initially treated with lenvatinib (12.9%). Other second‐line treatments included pembrolizumab, nivolumab, cabozantinib and ramucirumab. Hepatic function deteriorated during sequential systemic treatment in 48.6% of the patients as defined by an increase in at least one Child‐Pugh point. Median overall survival (mOS) from the start of first systemic treatment was 35 months for patients with sequential systemic treatment compared to 9 months for patients with one systemic treatment line ( P < 0.001). Patients previously treated with surgical/locoregional therapies had a longer mOS compared to patients with initial systemic treatment (66 vs 25 months; P = 0.020). Conclusions: Sequential systemic treatment is feasible and effective in selected patients with HCC in clinical practice. Our study underlines the critical importance of well‐preserved liver function for successful administration of sequential systemic therapy.